Perancangan Ilustrasi Buku “Patah Untuk Tumbuh” - Arief Hidayat Chaniago; Heldi Heldi (Institut Nalanda, 2023)
Heartbreak is a mental condition and social problem associated with teenagers who are failing in a romantic relationship. Heartbreak can occur in various circumstances, the end of a love story can be triggered by the end of a romantic relationship with a partner. This issue was raised as a paper by Apriyandisi under the pen name @berbagi_rasa. With the title